The clinical decision making process in the use of mobilisation with movement – A Delphi survey. (October 2020) - Baeske, R.; Silva, M.F.; Hall, T.
Abstract: Background: Mobilisation with movement (MWM) is a method of treating musculoskeletal disorders. Although widely used clinically and with increasing research investigation, little is known about the decision making process for its utilization. Objectives: To understand the factors experts believe important for utilization of MWM when assessing a patient, predicting responses to its delivery, responsive body areas, and expected outcomes to MWM . Design: A web-based Delphi study of experts in the use of MWM. Methods: Round one contained five open-ended questions regarding assessment strategies, prediction of successful and unsuccessful outcomes, body areas most responsive, and common outcome measures observed. Rounds 2 and 3 were quantitative and aimed at establishing consensus. Results: Thirty seven experts participated in the study and took part in round 1, thirty two in round 2, and twenty eight in round 3. The exclusion of red flags and impairment in range of motion (ROM), obtained the highest level of consensus for the item assessment strategies. Patient's presenting with a variety of issues on movement, in addition to mild to moderate levels of severity and immediately responsive to a trial MWM, were believed to respond favourably to MWM. Patients with predominant inflammatory pain, with high levels of psychosocial factors, increased central sensitization and not improving after a trial of MWM, were recognized as non-responders. Improvement of different aspects of movement (e.g. ROM, less fear) are the most common outcomes observed. Conclusions: This study provides factors believed to be important in the decision making process when using MWM clinically. Highlights: Clinical decision making in the use of mobilisation with movement. Web-based Delphi study. Diagnosis is based on movement assessment. Improvement of movement is the main outcome observed. Responsiveness of a trial of MWM is an important step of the decision making.